Study on synthesis of combination of silver nanoparticles and mesenchymal stem cell products for wound healing - Nguyễn, Thị Thanh Hoài (2020)
Overthe past few decades, silver nanoparticles (AgNPs) attractraptattention in wound treatmentdue to various featured natures such as the history of using silver, simple and effective synthesized methods, and above all the outstanding antimicrobial activity. These makeAgNPs become one of the most widely used agents for preventing infection. On the other hand,mesenchymal stem cells (MSCs)and products derived from MSCs, which appear as advanced therapies, have recently been studied and appliedinthe field of medicine. In termsof wound healing, many studies suggestthat paracrine signaling of MSCsrather than tissue differentiationand engraftment is a pivotalelement for promotingwound healing. That indicates the capacity to use conditioned medium (CM), which is one of the products derived from MSCsfor wound treatment. CM contains a variety ofcytokines, growth factors, chemokines that modulate the healing process through induction of re-epithelialization, angiogenesis,and remodeling. Therefore, we assume the synergistic effect of the combined use of AgNPs and CM, in which AgNPs with antibacterial, anti-inflammatory activities support CM to promote wound healing. Our target is chronic wounds that require advanced therapies for treatment. At the beginning of the research process, we aim to examine the healing effect of the combined use of AgNPs and CM on an acute wound, then perform it on a chronic wound model at a later stage. This thesis is the first step of research, so in thisstudy, threeobjectives need to be fulfilled